CHANGES IN THE EMPLOYMENT AND INCENTIVE SCHEME AS ELEMENTS OF CORPORATE RESTRUCTURING BASED ON THE EXAMPLE OF PKP CARGO - Anna Piotrkowska (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej, 2016)
The paper presents an example of restructuring in the area of employment and incentive scheme, which was conducted in one of the Polish companies operating in the transport industry. It shows the changes in the remuneration system, the level and structure of employment, and their impact on labour productivity and financial results of the analyzed entity.The analysis was conducted as a case study using data included in annual reports of the audited company. The aim of the paper is to draw the reader’s attention to the significance of controlling labour costs in the process of a company’s management.